ANALISIS PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN MENULIS TEKS LAPORAN HASIL OBSERVASI KELAS X IIS.1 SMAN 1 MENDOYO - Ni Putu Eka Puspita Dewi .; Prof. Dr. I Made Sutama,M.Pd .; Dra. Sang Ayu Putu Sriasih,M.Pd . (Jurnal Pendidikan Bahasa dan Sastra Indonesia Undiksha, 2015)
Penelitian ini bertujuan mendeskripsikan (1) penerapan model pembelajaran problem based learning dalam pembelajaran menulis teks laporan hasil observasi kelas X IIS.1 SMAN 1 Mendoyo dan (2) respons siswa X IIS.1 SMAN 1 Mendoyo terhadap penerapan model pembelajaran problem based learning dalam pembelajaran menulis teks laporan hasil observasi. Subjek penelitian ini adalah satu orang guru kelas 1 SMAN I Mendoyo dan siswa X IIS. 1 berjumlah 36 orang. Objek penelitian adalah penerapan dan respons terhadap model problem based learning dalam pembelajaran menulis teks laporan hasil observasi. Metode pengumpulan data yang digunakan adalah metode observasi, dokumentasi, dan wawancara. Data dianalisis dengan teknik analisis data deskriptif kualitatif. Hasil penelitian menunjukkan (1) penerapan model problem based learning pada siswa kelas X. IIS 1 SMAN 1 Mendoyo tergolong baik dan berhasil dilihat dari pemenuhan kriteria keterlaksanaan langkah pembelajaran dan skor yang dihasilkan siswa. Kunci keberhasilan keterlaksanaan model problem based learning adalah guru mampu merangsang keingintahuan siswa dengan permasalahan di sekitar siswa, mampu dalam mengarahkan siswa untuk bertanya, memberikan semacam penugasan dengan penggunaan waktu yang efisien, pembentukan kelompok heterogen. (2) Respon siswa terhadap penerapan model problem based learning dikatakan positif. Hal ini disebabkan oleh adanya situasi yang memungkinkan terjadinya kegiatan belajar optimal, pembelajaran dibangun dengan suasana dialogis dan proses tanya jawab terus menerus, pembelajaran dialog interaktif, model pembelajaran tidak monoton serta pemilihan materi yang otentik. Berdasarkan hasil penelitian ini, peneliti lain disarankan untuk meneliti lebih mendalam lagi tentang model problem based learning dan guru disarankan mampu menerapkannya sebagai salah satu alternatif dalam pembelajaran.Kata Kunci : problem based learning, menulis, teks, laporan hasil observasi This study was aimed at describing (1) the implementation of problem based learning instructional model in observation report text writing instruction in class X IIS.1 of SMAN 1 Mendoyo and (2) the response of the students in class X IIS.1 of SMAN 1 Mendoyo toward the implementation of problem based learning instructional model in observation report text writing instruction. The subjects of the study were a teacher of SMAN 1 Mendoyo teaching in class X and 36 students of SMAN 1 Mendoyo who were enrolled in class X IIS.1. Meanwhile, the objects of the study were the implementation of problem based learning instructional model in observation report text writing instruction and the students’ response toward it. The methods of data collection applied in this study were observation, documentation and interview. All the gathered data were then analyzed using descriptive-qualitative analysis. The result of the study revealed that (1) the implementation of problem based learning instructional model in observation report text writing instruction in class X IIS.1 of SMAN 1 Mendoyo could be categorized “good”. Moreover, regarding the fulfillment of the success criteria for the application of the instruction steps and the students’ scores, the implementation of problem based learning instructional model in observation report text writing instruction in class X IIS.1 of SMAN 1 Mendoyo was successful. The key of the success of the implementation of problem based learning instructional model was the fact that the teacher could stimulate the students’ curiosity toward surrounding problems, guide the students to question, give assignments to the students within efficient time and form heterogeneous students groups. (2) The response of the students in class X IIS.1 of SMAN 1 Mendoyo toward the implementation of problem based learning instructional model in observation report text writing instruction was positive. It was due to the fact that there was a situation that enabled the optimum learning process to happen, a situation that enabled dialogue among the students to happen, an interactive situation and ongoing question-and-answer process during the instructional process. It was also due to the instruction was not monotonous and the materials used were authentic. Concerning the result of the present study, it is suggested to other researchers to conduct deeper studies on problem based learning instructional model. It is also suggested to teachers to implement this model in their instruction as one alternative. keyword : problem based learning, writing, text, observation report